2010
DOI: 10.1128/ec.00200-09
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Genetic Mechanisms Lead to Loss of Functional TbAT1 Expression in Drug-Resistant Trypanosomes

Abstract: The P2 aminopurine transporter, encoded by TbAT1 in African trypanosomes in the Trypanosoma brucei group, carries melaminophenyl arsenical and diamidine drugs into these parasites. Loss of this transporter contributes to drug resistance. We identified the genomic location of TbAT1 to be in the subtelomeric region of chromosome 5 and determined the status of the TbAT1 gene in two trypanosome lines selected for resistance to the melaminophenyl arsenical, melarsamine hydrochloride (Cymelarsan), and in a Trypanoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…It is also noteworthy that T. b. rhodesiense STIB 871 and T. b. brucei STIB 940 are susceptible to melarsoprol and pentamidine in vitro although both carry the TbAT1 r allele. Loss of TbAT1 function has been described without mutations in the open reading frame of the gene [32]. However, since in the present study all isolates with a ‘wild-type’ TbAT1 ORF were fully susceptible to diminazene, we conclude that they possess a functional TbAT1 (i.e.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…It is also noteworthy that T. b. rhodesiense STIB 871 and T. b. brucei STIB 940 are susceptible to melarsoprol and pentamidine in vitro although both carry the TbAT1 r allele. Loss of TbAT1 function has been described without mutations in the open reading frame of the gene [32]. However, since in the present study all isolates with a ‘wild-type’ TbAT1 ORF were fully susceptible to diminazene, we conclude that they possess a functional TbAT1 (i.e.…”
Section: Discussionsupporting
confidence: 43%
“…The genotypic status of TbAT1 , located proximal to a telomere on chromosome 5 [32], has been more intensely investigated. Point mutations in TbAT1 were described, both in selected lab strains and in clinical T. brucei ssp.…”
Section: Introductionmentioning
confidence: 99%
“…AT1 has been found to be mutated, deleted, or down-regulated in melarsoprol-resistant trypanosomes (10,42) but AT1 knockout generated cells with only a twofold increased resistance to both melarsoprol and pentamidine (14), and there is evidence for resistance that is independent of AT1 disruption (43,44). Our results now show that AQP2, when defective, could explain cases of innate MPXR and/or acquired MPXR of clinical relevance.…”
Section: Discussionmentioning
confidence: 54%
“…In vitro and in vivo selected melarsomine-resistant T. b. evansi (Suswam et al 2001) revealed that the decrease in P2/ Tb AT1 transporter activity was linked both to reduced transporter expression and changes in binding properties (Suswam et al 2003). In a T. b. brucei strain selected for melarsomine resistance in mice the TbAT1 gene was still present but its transcript was lost (Stewart et al 2010). The lack of authentic orthologues of Tb AT1 and Tb AQP2 in T. congolense and T. vivax (see subsection Diminazene aceturate above) may explain why the drug is less potent against these parasites.…”
Section: Veterinary Trypanocides: Dosage Pharmacokinetics Mode Of Amentioning
confidence: 99%
“…For T. brucei group parasites it has been shown that mutations in TbAT1 and TbAQP2 genes can underlie resistance to both melaminophenyl arsenicals and to diamidines such as pentamidine (Graf et al 2015; Munday et al 2015 a , b ). The TbAT1 gene is also mutated in T. brucei group parasites (including T. b. evansi and T. b. equiperdum ) when selected for diminazene resistance (Barrett et al 1995; Stewart et al 2010). Also, in T. brucei loss of the amino acid transporter Tb AAT6 underlies resistance to the human African trypanocide eflornithine (Vincent et al 2010; Schumann et al 2011; Alsford et al 2012).…”
Section: Tests For Resistance Detectionmentioning
confidence: 99%